Teleworking - Saco Barrios, Raúl (2007)
This article deals with the study of telecommuting through the use of telecommunications or, better known as teleworking. Through this contribution, the author provides a comprehensive analysis of this phenomenon whose impact has been increasing in the modern world of work. To that extent, the author begins by developing the concept of telework, which is broad and can cover different definitions, however, it is understood that it can be understood as the work that is done remotely through the use of telecommunications by a person. Under that premise, the modalities of telework are also exposed, as well as the advantages and disadvantages of the same for both workers and employers. The article concludes by pointing out some relevant legal aspects to be taken into account in this modality of work, such as workers' rights, social security, data protection, among others.